Microneedling and platelet-rich plasma (PRP) treatment for mixed melasma - Wulandari, Puteri; Jusuf, Nelva Karmila; Nasution, Khairina (Journal of General - Procedural Dermatology and Venereology Indonesia, 2022)
Background: Melasma, or chloasma, is an acquired pigmentary disorder caused by increased melanin in the epidermal and dermal layers, characterized by brown or gray patches on the face and neck. There are many treatment options available; however, the difficulties in treating melasma are frequent recalcitrants, high recurrence rate, irregularity in treatment, and the tendency of the patients to self-medicate.Case Ilustration: We report a case of mixed melasma treated by microneedling and topical PRP administration. Thirteen weeks following the therapy, the patient showed a favorable response brighter skin and substantial disappearance of brown patches.Discussion: Studies assessing the efficacy of microneedling and platelet-rich plasma (PRP) treatment for melasma are still lacking. However, melasma improvement has been reported in patients treated with microneedling and PRP. In this study, we provided a study of a patient with mixed melasma treated by microneedling and PRP, which showed a favorable improvement.Conclusion: Microneedling and PRP treatment showed a favorable response in a patient with melasma, with substantial disappearance of brown patches and a decrease in MASI (Melasma Area and Severity Index) score.